Implementation of the INTERGROWTH‐21st Project in Brazil. Issue 9 (17th May 2013) - Silveira, MF; Barros, FC; Sclowitz, IKT; Domingues, MR; Mota, DM; Fonseca, SS; Mitidieri, A; Leston, AR; Knight, HE; Cheikh Ismail, L; ,
Abstract : Please cite this paper as: Silveira M, Barros F, Sclowitz I, Domingues M, Mota D, Fonseca S, Mitidieri A, Leston A, Knight H, Cheikh Ismail L, for the International Fetal and Newborn Growth Consortium for the 21 st Century (INTERGROWTH‐21 st ). Implementation of the INTERGROWTH‐21 st Project in Brazil. BJOG 2013; 120 (Suppl. 2): 81–86. The Latin American site in the INTERGROWTH‐21 st Project was Pelotas, Brazil, with approximately 4000 births per year. The sample for the Newborn Cross‐Sectional Study (NCSS) was drawn from four hospitals, covering 99% of births in the city. The Fetal Growth Longitudinal Study (FGLS) sample was recruited from one of the largest private ultrasound clinics in the city and 30 smaller, private, antenatal clinics serving middle to high socio‐economic status women. Among this site's major challenges was the recruitment of women for FGLS from numerous different clinics. Several public relations activities were conducted to improve collaborative efforts between the research team and obstetricians, paediatricians and community leaders in Pelotas.